PTH-067 Incidental Diagnosis of Inflammatory Bowel Disease in A British Bowel Cancer Screening Cohort: 6-Year Clinical Outcome of The First Reported Cohort. (17th August 2016) - Scott, J; Nosegbe, U; Butcher, R; Abbasi, A; Prudham, R; George, R; Limdi, J
Abstract : Introduction: The UK Bowel Cancer Screening programme (BCSP) was launched in 2006 in England and Wales, screening individuals aged 60–69 years with a Faecal Occult Blood test (FOBt) followed by a screening colonoscopy if FOBt positive. We reported the first ever experience of incidental diagnosis of Inflammatory bowel disease (IBD) through screening in 2012. We present a 6 year follow-up of this cohort. Methods: We conducted a retrospective case record review of clinical outcomes until 31 st December 2015 for patients diagnosed with IBD from the BCSP from April 2008 until September 2011. We reviewed their symptoms at diagnosis, treatment course and compared stage of disease at initial presentation to that at last follow-up. Results: Between April 2008 and September 2011, 136, 811 patients were invited to the BCSP and 67, 485 were screened with a 49.33% uptake and FOBt positivity of 2.02%. Colonoscopy was performed in 1401 patients and 13 patients (3 female) were diagnosed with IBD. Of these, 6 patients had Ulcerative colitis (UC), 5 had Crohn's disease (CD), 2 had IBD-unclassified (IBDU). One IBDU patient was subsequently re-classified as UC during follow-up. At diagnosis 7 (53.8%) patients were asymptomatic. An asymptomatic patient died of an unrelated cause, with follow-up data available for 12 patients. Median follow-up time was 80 months (range 39–87 months). Using the Montreal classification the distribution for UC included E1 (2), E2 (2) and E3 (2) and in CD showed L2 (7). Four CD patients had B1 disease and 1 had B2. Disease progressed in 2 patients and all 6 (100%) asymptomatic patients developed symptoms during follow-up. Treatment included steroids (10), 5 ASA (12), Azathioprine (6); Methotrexate (1) and Anti-TNF (Infliximab (2); Adalimumab (1)). Median time to immunomodulator was 29.5 months and to anti-TNF, 28.0 months. Mean CRP at diagnosis for those who progressed to Immunomodulator was 10.4 compared to 5.5 in those that didn't and 15.5 in those that required biologics. A patient with symptomatic IBDU underwent subtotal colectomy 54 months after diagnosis but died 7 days post-operatively. Another patient died at 39 months from an unrelated cause. Conclusion: Incidental diagnosis of IBD presents an important model for the study of early disease. A proportion of initially asymptomatic patients demonstrate disease progression with a rapid requirement for treatment escalation. Disclosure of Interest: None Declared